2009
DOI: 10.1002/jbm.b.31490
|View full text |Cite
|
Sign up to set email alerts
|

Textile for heart valve prostheses: Fabric long‐term durability testing

Abstract: The rapid developments and success in percutaneous vascular surgery over the last two decades with the now common stent grafts implantation, make the noninvasive surgery technique today attractive even for heart valve replacement. Less traumatic for the patient and also less time consuming, percutaneous heart valve replacement is however at its beginning and restricted to end of life patients. The noninvasive procedure expects from the heart valve prosthesis material to be resistant and adapted to folding requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Heim et al showed that a textile polyester could be considered as an alternative solution to replace valve leaflets. [9][10][11][12] Textile is a discontinuous material obtained from the assembling of individual fibers. Moreover, polyester is a standard biomaterial that has been already used extensively in vascular implants (e.g., arterial and stent grafts).…”
Section: Introductionmentioning
confidence: 99%
“…Heim et al showed that a textile polyester could be considered as an alternative solution to replace valve leaflets. [9][10][11][12] Textile is a discontinuous material obtained from the assembling of individual fibers. Moreover, polyester is a standard biomaterial that has been already used extensively in vascular implants (e.g., arterial and stent grafts).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it possessed enhanced resistance to calcification and thrombosis with superior in vivo biostability [20]. Furthermore, textile, less fragile polyester-based leaflets were designed as alternative to xenogenic, biologic materials [21,22]. Based on these examples can be stated that also synthetic, polymeric materials could be an alternative replacement for valve leaflets.…”
Section: )mentioning
confidence: 99%
“…As recommended TAVI are established for the treatment of highrisk, multimorbid patients with severe aortic stenoses which are no candidates for the open-heart surgical replacement. Since it is known that biological valves based on xenogenic pericardium tend to calcify and have a decreased durability in comparison to mechanical valves [19] also valve materials based on synthetic polymers, such as polycarbonate urea urethanes and polyesters, are under consideration [20][21][22][23]. These examples demonstrate impressively that polymers became more important also for cardiological applications.…”
Section: State Of the Artmentioning
confidence: 99%
“…These materials are expected to offer prolonged durability compared with that seen in current biological valves, and feature all the possible attributes of the ideal implant in blood flow (biocompatibility, fatigue resistance, elimination of the risk of valve apparatus fracture, resistance of immunitymediated processes, resistance to calcium deposition, and antithrombogenic surface). It would then be sufficient if the novel material possesses at least the properties identical to those seen in current components of mechanical valves [6,7] . Several materials that have shown promise to meet these requirements are currently available [8,9] .…”
Section: Valves Placed Within Tubular Systemsmentioning
confidence: 99%